Mendorong Visibilitas dan Responsivitas Layanan Usaha Mikro melalui Integrasi Google Maps dan WhatsApp Business - Khotim Fadhli; Nia Aprilia Bisari; Bekti Widyaningsih; Muhyiddin Zainul Arifin; Moh. Faridl Darmawan; Siti Munawaroh; Anggun Dwi Cahyaningrum; Muhammad Syauqi Murtadlo; Muhammad Zakky Alfadani; Shoviatun Nur Aini (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
This community service program addresses the digital transformation gap between urban and rural areas that limits market reach for micro-entrepreneurs in Palrejo Village, Sumobito District, Jombang Regency. The activities focus on improving visibility, credibility, and service responsiveness by using Google Business Profile as an information showcase and WhatsApp Business as a customer communication channel. The program aims to establish complete and verified business profiles, provide product catalogs, and cultivate consistent and ethical management of digital identity. The approach employed is Participatory Action Research, with stages that include joint planning with the village government and business owners, face-to-face training, door-to-door mentoring, and monitoring of simple metrics, such as profile views, route requests, and customer conversations. The results show that ten business profiles were created and verified, most participants activated product catalogs and automated messages, and early increases in reach indicators began to appear. Local leaders emerged to support their peers, post-transaction review requests became a habitual process, and information updates were carried out more regularly. Recommendations include regular digital clinics, a minimum standard for village digital business identity, and a monthly monitoring panel to sustain behavioral change and enhance economic impact.